Using In silico Tools to Analyze the 5ʹ Untranslated Regions of the Alcohol Dehydrogenase Gene from Arabidopsis thaliana and Omega Sequence - Mohammadhassan, Reza; Asadishad, Tina (UI Scholars Hub, 2023)
The 5ʹ ends of protein-encoding genes contain 5ʹ untranslated regions (5ʹUTRs), which can effectively participate in regulating gene expression. The 5ʹUTRs of Arabidospis thaliana–derived alcohol dehydrogenase gene (AtADH) and omega (Ω) sequence from tobacco mosaic virus (TMV) are the most effective enhancers in biotechnology. In this study, bioinformatics techniques were employed to analyze the characteristics of the above sequences. After 5ʹUTR sequence collection, the inner ribosome entrance sites; small RNA (sRNA) target sequences; nucleotide contents; and upstream start and stop codons, ORFs, and coding DNA sequences of the Ω sequence and AtADH 5ʹUTR were identified. Moreover, the free energies of secondary structures were calculated. Both 5ʹUTRs lacked upstream start codons and proteins, causing no interruptions in ribosome activity. The GC contents of the Ω sequence and AtADH 5ʹUTR were 24% and 30%, respectively. The Ω sequence contains more pyrimidines than AtADH 5ʹUTR. The Ω sequence included only three CAAT box regulatory elements. The free energy of the secondary structures of Ω was less than that of the AtADH 5ʹUTR. Two predicted secondary structures of Ω showed low complexity and free energy. Ω had a longer Inner ribosome entrance sites than the AtADH 5ʹUTR. In contrast to the AtADH 5ʹUTR, Ω was targeted by two sRNAs. Therefore, Ω is more powerful in enhancing ribosomal activity, translation, and protein expression than the AtADH 5ʹUTR.